2018
DOI: 10.1002/adfm.201802503
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Extracellular Imaging of Biochemical Cell Activity Using InGaN/GaN Nanowire Arrays as Nanophotonic Probes

Abstract: The application of InGaN/GaN nanowire heterostructure arrays as photonic probes for dynamic imaging of biochemical and cellular processes in an incident light fluorescence microscope is demonstrated. The photoluminescence intensity of InGaN/GaN nanowires sensitively depends on the pH value of the surrounding solution, making them suitable probes for the optical detection of biochemical processes accompanied by local pH variations. Grown on a conductive substrate, the nanowire arrays can be operated in a well-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…New materials and breakthrough technologies are increasingly necessary to conserve energy and develop environmentally friendly energy sources. Tremendous efforts have been made to overcome the emerging environmental problems [6][7][8][9][10][11][12][13]. With the advent of cutting-edge technologies, hydrogen is one of the most prominent candidates as an ecosystemfriendly and reusable energy source [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…New materials and breakthrough technologies are increasingly necessary to conserve energy and develop environmentally friendly energy sources. Tremendous efforts have been made to overcome the emerging environmental problems [6][7][8][9][10][11][12][13]. With the advent of cutting-edge technologies, hydrogen is one of the most prominent candidates as an ecosystemfriendly and reusable energy source [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A large variety of different growth techniques in combination with their promising properties, such as high crystalline quality, 1 one-dimensionality, 2 and variability for functionalization, makes semiconductor NWs interesting for a wide field of applications ranging from transistors and solar energy harvesting, 3 light-emitting diodes and laser diodes, 1,[4][5][6] to photodetectors, waveguides, 4,7 and optochemical sensors. [8][9][10] Group-III-V NWs have attracted particular interest due to the tunability of the direct bandgap and improved material quality compared to bulk materials. 1,11 It has been shown that InGaN NW light-emitting diodes exhibit a reduced Auger recombination rate, i.e., a lower efficiency droop, 3 compared to bulk InGaN or InGaN quantum wells (QWs).…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional (1D) nanomaterials have received extensive research interest in recent years along with the vast development of microelectronics, 1 energy, 2 environment, 3 biology, 4 and other fields. Similar to the applications of bulk materials, nanomaterials in integration and practical applications are subjected to mechanical deformation, especially in flexible devices and single nanowire (NW) based electronics.…”
Section: Introductionmentioning
confidence: 99%